A 'Brazilian way'?: characteristics and challenges of Brazil's development assistance in Africa - Rasconi, Davide (Department of Political Studies, 2017)
Brazil development cooperation in Africa has been increasing significantly since the beginning of the new millennium. This paper examines both characteristics and challenges of such cooperation, with regards to the centuries-old linkages that tie the two shores of the Atlantic and the historical impact that Africa has had on Brazil. The main focus is on development cooperation in the continent after Lula's election in 2003, highlighting both domestic and international factors that allowed this cooperation to rapidly increase, while analysing the ongoing Brazilian crisis undermining it. The final consideration is that Brazil's development cooperation is characterized by the duality of national interests on one side, where it is seen as an important tool of foreign policy, and its humanitarian aspect together with the empowerment of local populations on the other. This paper concludes by arguing that a 'Brazilian way', indeed, exists.